India’s Transition towards Green Economy (British Journal of Multidisciplinary and Advanced Studies, 2023)
The agricultural sector’s contribution to India’s Gross Domestic Product (GDP) has dropped from 17.4% in 2006-07 to 14.2% in 2010-11i, while the manufacturing sector has underperformed, accounting for only 20% of GDP, due to high interest rates, infrastructure bottlenecks, slow decision-making by the government, and weak domestic demand Furthermore, the service sector, which accounts for nearly 65% of GDP, has also been losing its momentum due to segments like the banking and real estate facing demand and investment constraints. Furthermore, the environment has suffered gravely with the economic progress as from 1990 to 2008, India’s GDP per capita rose by an impressive 120% leading to the natural capital to decline by 31 % in the same period. Adding to that, currently India is operating on almost twice its bio-capacity; indicating that the population’s demand from the ecosystem exceeds the capacity of that ecosystem to regenerate the resources.  To ensure that inter-linkages between the economic, societal, and environmental aspects of development are overarching, India needs vital transitions. A green economy strengthens pro-poor economic growth by building up natural capital and secures livelihood options of the poorIn the light of the above Context, this paper attempts to understand the key sectors for intervention in India and have emerged as the main players in undertaking green initiatives. These sectors have contributed to economic growth of the nation while simultaneously causing detrimental effects on the environment. Section 2 of the paper makes an analysis of the six sectors that have the potential of contributing towards achieving the balance along the three pillars of sustainability. Section 3 further analyses the dominant barriers faced by some of the initiatives and how they can possibly be overcome.   Finally it the    foundation for further research and understanding the viable agents of changes for bringing about this transition.